Calcareous Nanofossil of Post-Gondwana Sequence in Southern Banda Arc, Indonesia - Angga Jati Widiatama; Lauti Dwita Santy; Rikza Nur Faqih An Nahar; Zulfiah; Winda Eka Mandiri Puteri; Adrianus Damanik; Rubiyanto Kapid (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
The presence of calcareous nannofossils in samples of the Post-Gondwana sequences (Kolbano and Viqueque sequence) gives guidance about the relative age of the study area located in the Outer Banda Arc, namely Timor, Rote, and Sawu Island. The study was carried out on six traverses, Timor Island traverse (Baun and Camplong), Rote Island traverse (Termanu and Central Rote), and Sawu Island traverses (West Sawu and East Sawu). There is 29 outcrop sample prepared using the smear slide method and observed using a polarizing microscope with 1000x magnification. The results of the study showed the presence of Cretaceous, Paleogene, and Neogen-Quarternary calcareous nannofossil. There are 82 species from 14 families identified in the post-Gondwana sequence. The results showed that the assemblage of calcareous nannofossil in Cretaceous characterized by the presence of Watznaueria fasciata, Watznaueria cynthae, Cyclagelosphaera brezae, Orastrum campanensis, and Micula concava. The assemblage of Paleogene calcareous nannofossil characterized by the presence of Coccolithus staurion, Chiasmolithus solitus, Discoaster minimus, Tawelus (?) magnicrassus, Chiasmolithus bidens, Prinsius africanus, Cyclicargolithus luminus, Spenolithus elongatus, Reticulofenestra umbilica, Cruciplacolithus vanheckae, and Helicospharea seminulum, and the assemblage of Neogene calcareous nannofossil characterized by the presence of Reticulofenestra pseudoumbilica, Discoaster quinqueramus, Helicosphaera princei, and Discoaster pansus. Quarternary calcareous nannofossil characterized by the presence of Ponthospaera indooceanica.